2007
DOI: 10.1029/2006ja011896
|View full text |Cite
|
Sign up to set email alerts
|

Long‐period oscillations at discrete frequencies: A comparative analysis of ground, magnetospheric, and interplanetary observations

Abstract: [1] The power spectra of remarkable events of long-period fluctuations of the geomagnetic field (as identified at a low-latitude station, L'Aquila, l % 36°) reveal a tendency for a repeated occurrence of power enhancements in the same frequency bands (f % 0.9-1.0, 1.2-1.4, 2.1-2.3, 2.5-2.7 mHz), often coincident with CMS frequencies. In four cases the data availability and the results of the spectral analysis allowed unambiguous conclusions on the correspondence between ground, magnetospheric, and solar wind f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
6
30
0
Order By: Relevance
“…Their event occurred under a solar wind condition of stable northward IMF direction (almost tangential to the magnetopause), and high solar wind speed (620 km/sec). December 13 event was not associated with large solar wind disturbances as the event examined by Shimazu et al (1995) and other events examined by Villante et al (2007). Geomagnetic responses in low latitudes are essentially similar to events analyzed by them.…”
Section: December 13 1999supporting
confidence: 58%
See 1 more Smart Citation
“…Their event occurred under a solar wind condition of stable northward IMF direction (almost tangential to the magnetopause), and high solar wind speed (620 km/sec). December 13 event was not associated with large solar wind disturbances as the event examined by Shimazu et al (1995) and other events examined by Villante et al (2007). Geomagnetic responses in low latitudes are essentially similar to events analyzed by them.…”
Section: December 13 1999supporting
confidence: 58%
“…Villante et al (2007) suggests that geomagnetic fluctuations can be driven directly by fluctuations of the solar wind density at the same frequencies. On the other hand, the repeated occurrence in the same frequency bands and some evidence for amplification processes suggest additional contributions possibly related with cavity/waveguide resonances.…”
Section: December 13 1999mentioning
confidence: 99%
“…On the other hand, a clear correlation between the variations of the H component and the variations of the SW dynamical pressure on time scales of few minutes was found in a case study by Francia et al (1999). This aspect has been corroborated recently by Villante et al (2005b), who presented a joint analysis of SW, magnetospheric and ground observations, and showed that remarkable ground events at "selected" frequencies found a clear correspondence in the magnetospheric field at geostationary orbit, as well as in the SW density (and dynamical pressure). In addition, Kessel et al (2004) found ULF fluctuations in the Pc5 range in high speed streams, compressional in the leading edge and Alfvènic in the central region.…”
Section: Low Frequency Magnetospheric Modes During the Stormsupporting
confidence: 55%
“…Other studies have shown similarities between individual discrete solar wind compressional oscillations and global magnetospheric pulsations observed in geosynchronous magnetic fields [Kepko and Spence, 2003] and in low latitude ground based magnetometer measurements [Villante et al, 2007]. Kessel et al [2004] reported that total Pc5 power of Alfvenic and compressional fluctuations in high speed solar wind streams was correlated with total Pc5 power of ground-based magnetic field pulsations.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, during individual high speed events they observed discrete frequency ULF fluctuations in the 1 -4 mHz band in the solar wind but no one-to-one correspondence with the ground-based frequencies. Except for Villante et al [2007] who included some coherence spectra results, all of these studies have used frequency, amplitude, and direct time series comparisons. However, spectral cross-phase is an additional parameter which can be exploited.…”
Section: Introductionmentioning
confidence: 99%